2003
DOI: 10.1161/01.cir.0000045666.04794.14
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressor Response to Angiotensin II Infusion in Patients With Chronic Heart Failure Receiving β-Blockers

Abstract: Background-A synergistic interaction between the angiotensin II (Ang II) type 1 receptor and ␣ 1 -adrenergic receptors has been described. We hypothesized that the nonselective ␤-antagonist carvedilol, through its ␣ 1 -adrenergic blocking properties, may modulate vascular reactivity to Ang II in patients with chronic heart failure (CHF). Accordingly, we compared the vasopressor response to infused Ang II in patients treated with carvedilol and metoprolol, a selective ␤-antagonist. Methods and Results-All subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This effect could be related to the results obtained by Vittorio et al, where the treatment with metoprolol and carvedilol produced an increase in BP in response to Ang-II infusion. 24 In relation to the combination therapy, the antihypertensive mechanisms are not sufficiently studied. In this way, through synergist mechanism, the use of interactions decreased the BP by using lower doses of captopril and propranolol, 25 these results were corroborated by us with this combination.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be related to the results obtained by Vittorio et al, where the treatment with metoprolol and carvedilol produced an increase in BP in response to Ang-II infusion. 24 In relation to the combination therapy, the antihypertensive mechanisms are not sufficiently studied. In this way, through synergist mechanism, the use of interactions decreased the BP by using lower doses of captopril and propranolol, 25 these results were corroborated by us with this combination.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that irbesartan treatment attenuated vasopressor response to NA, PE, and ME, whereas interactions between RAAS and SNS have already been established [ 18 ], and this can be confirmed from the study done by Raasch et al, wherein the systemic vascular responses to NA were diminished after pretreatment with losartan [ 67 ]. However, Ang-II suggests facilitating sympathetic neurotransmission at various sites such as CNS and presynaptic sympathetic nerve terminals [ 68 ]. Additionally, there are findings that in hyperinsulinemia scenarios, pioglitazone enhances adrenergic neurons' control over the blood vessels [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacodynamics is such that blood pressure increases within minutes, is sustained at a fixed infusion rate, and returns to preinfusion values within minutes after cessation of the infusion (50). As such, direct links between dosages and changes in organ system responses could not be obtained across all studies.…”
Section: Discussionmentioning
confidence: 99%